2022
DOI: 10.3847/1538-4357/ac3753
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Induced Anisotropies in the Arrival Directions of Ultra-high-energy Cosmic Rays from Nearby Radio Galaxies

Abstract: Detailed simulations of the arrival directions of ultra-high-energy cosmic rays are performed under the assumption of strong and structured extragalactic magnetic field (EGMF) models. Particles leaving Centaurus A, Virgo A, and Fornax A are propagated to Earth, and the simulated anisotropic signal is compared to the dipole and hotspots published by the Pierre Auger and Telescope Array Collaborations. The dominance of the EGMF structure in the arrival directions of events generated in local sources is shown. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Apart from Centaurus A, also Fornax A (NGC 1316) and Virgo A (NGC 4486) stand out in terms of their extraordinarily high radio flux in the local (< 21 Mpc) Universe. Adding these sources yields also some benefit in explaining the observed arrival directions [26,28]. In addition, several studies have demonstrated that the UHECR spectrum and composition are consistent with UHECRs originating in radio galaxies [29][30][31].…”
Section: Introductionmentioning
confidence: 96%
“…Apart from Centaurus A, also Fornax A (NGC 1316) and Virgo A (NGC 4486) stand out in terms of their extraordinarily high radio flux in the local (< 21 Mpc) Universe. Adding these sources yields also some benefit in explaining the observed arrival directions [26,28]. In addition, several studies have demonstrated that the UHECR spectrum and composition are consistent with UHECRs originating in radio galaxies [29][30][31].…”
Section: Introductionmentioning
confidence: 96%
“…In addition to the large-scale anisotropy, the Pierre Auger and the Telescope Array Observatories detected regions in the sky with a relative excess of events. The Pierre Auger Collaboration reported two hotspots regions (HS1 and HS2) for events with energy above 60 EeV [32] centered approximately at (305 • , 25 • ) and (290 • , −70 • ) [33] in galactic coordinates. The Telescope Array Collaboration reported one hotspot (HS3) for events with energy above 57 EeV centered at (146 • .7, 43 • .2) in equatorial coordinates [34].…”
Section: Introductionmentioning
confidence: 99%
“…The size of the magnetic horizon varies significantly with the direction (Hackstein et al 2016). The flux at Earth from sources located in the interior of galactic clusters, for instance, Virgo A, is highly suppressed by the EGMF (Tanco 1998;de Oliveira & de Souza 2022). The angular power spectrum of the UHECR arrival direction is EGMFdependent.…”
Section: Discussionmentioning
confidence: 99%